The crystal structure of human dopamine β-hydroxylase at 2.9 Å resolution - Vendelboe, Trine V. (Sci Adv, 2016)
The norepinephrine pathway is believed to modulate behavioral and physiological processes, such as mood, overall arousal, and attention. Furthermore, abnormalities in the pathway have been linked to numerous diseases, for example hypertension, depression, anxiety, Parkinson’s disease, schizophrenia, Alzheimer’s disease, attention deficit hyperactivity disorder, and cocaine dependence. We report the crystal structure of human dopamine β-hydroxylase, which is the enzyme converting dopamine to norepinephrine. The structure of the DOMON (dopamine β-monooxygenase N-terminal) domain, also found in >1600 other proteins, reveals a possible metal-binding site and a ligand-binding pocket. The catalytic core structure shows two different conformations: an open active site, as also seen in another member of this enzyme family [the peptidylglycine α-hydroxylating (and α-amidating) monooxygenase], and a closed active site structure, in which the two copper-binding sites are only 4 to 5 Å apart, in what might be a coupled binuclear copper site. The dimerization domain adopts a conformation that bears no resemblance to any other known protein structure. The structure provides new molecular insights into the numerous devastating disorders of both physiological and neurological origins associated with the dopamine system.